International graduate students’ experiences and intentions to stay in the United States - Foley, Lara; Atila Demir, Sevim (Journal of International Students, 2026)
This study examines the experiences of international graduate students at a private university in the south-central United States and explores their intentions to remain in the United States after graduation. Through semistructured interviews with eleven students, the research investigates how participants adapted to a new academic and cultural environment and how these experiences informed their future plans. The interview data were coded through a two-step process that involved first analyzing students’ initial arrival experiences and then identifying key factors shaping decisions about remaining in the United States. The findings highlight the interconnected roles of early challenges, institutional and national contexts, social support, and students’ personal circumstances and cultural backgrounds. Most participants planned to stay or considered staying depending on future conditions. A clear relationship emerged between initial adjustment difficulties, levels of social support, and postgraduate plans.